Calidad del servicio y su influencia en la satisfacción del cliente en el Banco de Crédito del Perú BCP, Iquitos - 2021 - Alves Milho Del Castillo, Heidi Priscila (2021)
The general objective of this research work is to determine how the quality of the service influences customer satisfaction at Credit Bank of Peru BCP, Iquitos agency - 2021, the method used is Quantitative, Descriptive - Correlational in nature. According to the quality of service study variable, there is 63% acceptance on average for the dimensions, so it can be deduced that the organization's facilities meet their requirements, as well as comply with the cleaning standards, the customers They perceive that the staff has the ability to provide the promised service accurately and regularly, they are willing to listen and solve their problems or emergencies in the most convenient way, quickly and helpfully, they demonstrate courtesy, as well as the ability to convey confidence. Regarding the satisfaction with the service in the care with 65% acceptance on average for the dimensions, they consider that the workers have the skills and qualities necessary to provide a good service and that this is especially to meet their needs and that The staff has adequate information about customers that contains aspects related to their needs, to determine the level of quality achieved, which demonstrates hypothesis 1 (H1): The quality of the service directly and positively influences satisfaction of the client of Credit Bank of Peru, Iquitos Agency - 2021.